Tailoring the pressure-drop in multi-layered open-cell porous inconel structures - Oun, Hatem; Kennedy, Andrew R. (Springer Verlag, 2015)
This study investigates the pressure-drop behaviour associated with airflow through bulk and structurally tailored multi-layered, open-cell porous Inconel structures over a wide airflow velocity range (0–50 m s-1). The effect of airflow velocity on the pressure-drop behaviour as a function of the sample thickness is presented and related to the flow behaviour corresponding to the relevant flow regimes (Darcy, Forchheimer, Turbulent and Postturbulent). Entrance effects are highlighted as a source of the pressure-drop increase for porous structures with air gaps, regardless of their sizes, as long as they are larger than those generated by loosely-stacked structures. The pressure-drops for gapped porous structures and the mathematical-summation of the pressure drop for the corresponding individual components, were in very good agreement, at lower airflow velocities. The potential for mass-efficient porous structures, providing a high pressure drop, was demonstrated using multiple thin porous laminates separated by air gaps.